The Post-Political Urbanity: Art and the Contested Public Sphere - Moraru, Cristina (CAP - Cadernos de Arte Pública / Public Art Journal, 2021)
We live in post-political times (Rancière 2004), when the fetishization of urbanity and technocracy creates the context of replacing the usual terms of describing the city with regard to neo-liberal thinking as competitiveness, creativity, sustainability, globality – terms that have been finding their applicability simultaneously, in a material and discursive manner. Thus, the city is being approached in terms of the competitive city, the creative city, the sustainable city, the global city, considering different perspectives over masses and class distinctions, which presuppose a special relation between singularity and universality: a singularity of its proper name – as the post-political city (Swyngedouw, 2010) – and an absolute universality of the action of the masses.